The relationship of emotional intelligence with mental health and demographic factors in army soldiers - H Shahmiri; J Moradzadeh; F Ostad mohammadali; AM RaahNejat (فصلنامه ابن سینا)
Background: A high emotional intelligence and mental health makes soldiers immune to the problems and leads them to more conformity in military fields. This study aimed to investigate the relationship of emotional intelligence with mental health and demographic factors in IR army soldiers.